STUDI PELAKSANAAN DIKLAT JURNALISTIK MAHASISWA TINGKAT DASAR UNIT KERJA MAHASISWA BAHANA MAHASISWA UNIVERSITAS RIAU - Ahlul Fadli; Wilson '; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine how to provide education and training for students of journalism in Taja by the Student Work Unit (UKM) Bahana Riau University Students. The main focus of this study was to determine the activity of journalism education and training of students. On the basis of this primary focus, then there are 15 sub focus into concentration. This type of research is descriptive qualitative case study approach. Data collection techniques in this research is by interview, observation and documentation on the informant, The results have been summarized in the 15 activities of an education and journalism training for students by SMEs Bahana Students at the University of Riau. From this process the participants have writing skills, through the process of a guardian or trustee Bahana SMEs through direct guidance and learn directly, task or assignment, by way of training and practice.